Students’ perception on putra fizik mobile application as a complementary teaching and learning tool for physics education - Zainuddin M.F.; Kamarudin S.; Omar M.K.; Mohd S.M. (Institute of Advanced Scientific Research, Inc., 2024)
Journal of Advanced Research in Dynamical and Control Systems, vol. 12, special issue-02, 2020